Predictors of Real-World Parents’ Acceptance to Vaccinate Their Children Against the COVID-19 - Galanis, Petros; Vraka, Irene; Siskou, Olga; Konstantakopoulou, Olympia; Katsiroumpa, Aglaia; Moisoglou, Ioannis; Kaitelidou, Daphne (Acta medica Lituanica, 2022)
Background: As the COVID-19 pandemic continues to threaten public health, the vaccination of children against the disease appears to be a key factor to control the pandemic. Our aim was to investigate the prevalence of parents who have vaccinated their children against the COVID-19 and the factors influencing this decision.Materials and Methods: We conducted a web-based cross-sectional study in Greece during the first week of September 2021. The study questionnaire was distributed through social media and a convenience sample was obtained. Only parents with children aged 12–17 years old could participate in the study. We collected socio-demographic data of parents and we measured their attitudes towards vaccination and COVID-19 pandemic.Results: Study population included 656 parents. Regarding vaccination, 27.1% of parents had their children vaccinated against the COVID-19, while almost all children had a complete vaccination history (98.9%). The most important reasons for decline of COVID-19 vaccination were doubts about the safety and effectiveness of COVID-19 vaccines (45.3%) and fear of side effects (36.6%). Regarding the information about the COVID-19 vaccines, parents showed more trust in family doctors than in scientists and the government. We found that increased parents’ age, increased trust in COVID-19 vaccines, and positive attitude of parents towards vaccination had a positive effect on children’s vaccination.Conclusions: Understanding the factors influencing parents’ decision to vaccinate their children against the COVID-19 is crucial to increase the COVID-19 vaccination coverage rate. Implementation of public health policies is necessary to spread knowledge about COVID-19 vaccines and to regain vaccine confidence.
Keywords: COVID-19; parents; vaccine uptake; children; Greece